2011
DOI: 10.4088/jcp.11r06927
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Term and Long-Term Efficacy and Effectiveness of Antipsychotic Medications for Schizophrenia

Abstract: Despite intraclass differences and the complexities of antipsychotic choice, the second-generation antipsychotics are important contributions not only to the acute phase but, more importantly, to the maintenance treatment of schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 0 publications
2
26
0
1
Order By: Relevance
“…The highly publicized primary endpoint finding was difference in time to discontinuation, which favored olanzapine, with improvement in psychopathology a secondary endpoint, which also slightly favored olanzapine (9). However, subsequent independent scrutiny of the design and data analysis of this study revealed serious flaws, leading to the conclusion that it was impossible to draw conclusions about the relative merits of the drugs from CATIE's findings (1,(68)(69)(70)(71). These flaws included allowing patients to remain on the same drug they had been receiving prior to randomization, which affected many of those randomized to risperidone or olanzapine (9), and olanzapine dosage up to 30 mg/day (9), three times the dose found to be effective for non-TRS (72).…”
Section: Use Of Atypical Apds In Non-treatment-resistant Schizophreniamentioning
confidence: 88%
“…The highly publicized primary endpoint finding was difference in time to discontinuation, which favored olanzapine, with improvement in psychopathology a secondary endpoint, which also slightly favored olanzapine (9). However, subsequent independent scrutiny of the design and data analysis of this study revealed serious flaws, leading to the conclusion that it was impossible to draw conclusions about the relative merits of the drugs from CATIE's findings (1,(68)(69)(70)(71). These flaws included allowing patients to remain on the same drug they had been receiving prior to randomization, which affected many of those randomized to risperidone or olanzapine (9), and olanzapine dosage up to 30 mg/day (9), three times the dose found to be effective for non-TRS (72).…”
Section: Use Of Atypical Apds In Non-treatment-resistant Schizophreniamentioning
confidence: 88%
“…Time to treatment failure offers an integrated measure of efficacy and tolerability that is clinically relevant and is perhaps more meaningful than using as a primary outcome measure a rating scale that measures psychopathology. 26 Time to treatment failure has been proposed to more accurately reflect drug effects, compared with all-cause discontinuation, because the latter outcome can include discontinuations that are not necessarily related to failure of the intervention. For example, it has been argued that in the context of the CATIE schizophrenia study, discontinuations "owing to patient's decision" (a component of all-cause discontinuation) may have reflected effects that were unrelated to drug treatment, such as subject dissatisfaction with study participation.…”
Section: Discussionmentioning
confidence: 99%
“…Olanzapine might lead to longer treatment maintenance than haloperidol or ziprasidone in treatment-naĂŻve people with a FEP [40]. Accordingly, Glick et al have reported in a metanalysis of medium and long-term effectiveness that olanzapine and risperidone appear to be the most effective antipsychotics in the treatment of schizophrenia and FEP [42]. …”
Section: Aiming For Efficacy and Effectivenessmentioning
confidence: 99%